Digital Learning Tools in Early Childhood Education: A Systematic Literature Review - Muhammad Wahyu Putra Buana; Muhammad Iqbal (Journal of Early Childhood Development and Education, 2026)
Background: The rapid advancement of digital technology has significantly influenced educational practices, particularly in early childhood education (ECE). Various digital learning tools have been introduced to support young children's learning experiences, yet their effectiveness and associated challenges remain a subject of ongoing discussion. Objective: This study aims to systematically review existing literature on the use of digital learning tools in ECE and to identify their educational benefits, challenges, and emerging research trends. Methods: A systematic literature review was conducted using the PRISMA framework. Relevant studies indexed in the Scopus database and published between 2018 and 2025 were identified, screened, and analyzed. Following the selection process, 96 studies met the inclusion criteria and were included in the review. Results: The findings reveal that digital learning tools positively contribute to children's cognitive development, learning engagement, creativity, language acquisition, and collaborative skills. However, several challenges were identified, including limited teacher digital competence, unequal access to technological resources, concerns regarding excessive screen time, and insufficient parental involvement. The results also emphasize the importance of aligning technology integration with appropriate pedagogical practices. Conclusion: Digital learning tools offer significant opportunities to enhance early childhood education when implemented effectively. Addressing existing challenges through teacher training, equitable access to technology, and stronger parental support is essential to maximize learning outcomes. The review provides valuable insights for educators, policymakers, and researchers in advancing technology-enhanced learning in ECE.